2012
DOI: 10.1177/0907568211429625
|View full text |Cite
|
Sign up to set email alerts
|

Unaccompanied asylum-seeking children: Whose perspective?

Abstract: Recent years have seen increasing attention being paid to unaccompanied asylum-seeking children. This article provides an overview of research in the field and its implications for an understanding of these children as a particularly vulnerable category. The existing research focuses primarily on investigating the children's emotional well-being from psychiatric and medical perspectives. M oreover, in these studies such emotional problems tend to be linked to previous and current traumatic experiences, in part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
69
0
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(79 citation statements)
references
References 23 publications
0
69
0
8
Order By: Relevance
“…In addition they differ in terms of reasons for travelling (family related, exploitation related, survival related or independent child migration), how the journey is made (travelling entirely alone, with an adult who abandons them shortly after arrival or with an adult who may be caring for them or exploiting them), and their present life situation (; Wernesjö, 2012;Bhabha, 2014). These heterogeneous experiences suggest that policy makers, social workers and other practitioners should avoid the tendency towards generalisation and focus attention on the response to individual need of UAMs.…”
Section: Perspectives On Unaccompanied Minors -Complexity Vulnerabilmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition they differ in terms of reasons for travelling (family related, exploitation related, survival related or independent child migration), how the journey is made (travelling entirely alone, with an adult who abandons them shortly after arrival or with an adult who may be caring for them or exploiting them), and their present life situation (; Wernesjö, 2012;Bhabha, 2014). These heterogeneous experiences suggest that policy makers, social workers and other practitioners should avoid the tendency towards generalisation and focus attention on the response to individual need of UAMs.…”
Section: Perspectives On Unaccompanied Minors -Complexity Vulnerabilmentioning
confidence: 99%
“…Foster care is viewed to be more appropriate to the needs of UAMs who are living with many social and personal problems in an unfamiliar society without the support and guidance of their parents or carers (Derluyn and Broekaert, 2007;Hodes et al, 2008). In these situations, it is argued, UAMs require the care of appropriate adults to help them manage their life situation (Wernesjö, 2012). The SCEP (2009) suggests that every separated child should have the opportunity to be placed within a family, if it is in their best interests, pointing to the need for consistent adults in their lives.…”
Section: Benefits Of Foster Care Provisionmentioning
confidence: 99%
“…). Wernesjö () argues that a category specifically emphasizing the children's background experience might be added to this division, one which may be similar to the research covering children's pre‐flight experiences (Thomas et al . ; Hopkins & Hill ).…”
Section: Previous Research About Unaccompanied Minorsmentioning
confidence: 99%
“…). However, research on unaccompanied minors tends to focus primarily on mental health issues from a medical perspective (Wernesjö ). Thus, there are still gaps that warrant further study; this is also confirmed in the Nordic research context, which is a growing research field (e.g.…”
Section: Previous Research About Unaccompanied Minorsmentioning
confidence: 99%
“…Despite a long tradition of upholding the rights of children and the ro le this plays in national identity (Bak & von Brömssen, 2013), the views of children and young people in inspections of the Swedish residential care system are limited (På lsson, 2015). Such first hand accounts as exist, have commonly focussed on pre-care experiences (Wernesjo, 2012) with an assumption that the journey and its antecedents are the cause of trauma (Bradby et al, 2015 (Stretmo, 2014: 236) For those in residential settings, the difficulty of establishing social contact especially with Swedish peers gave rise to isolation for unaccompanied boys. Once they left care, they said that their migration experiences were linked to feelings of difference and a lack of 'belongingness' (Söderqvist, 2013).…”
Section: The Swedish Literaturementioning
confidence: 99%